IMPLEMENTASI PELATIHAN DAN PENDIDIKAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI STMIK STIKOM BALI - I Gede Kt. Tjahyadi Putra Budhi (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
STMIK STIKOM Bali is one of the private universities in Bali. During the course of the development of leadership and culture in universities many have had a change. The main factor that has changed in the organizational culture is the development of technology and the increasing number of human resources. Organizational culture in a company that is a university is carried out to achieve the goals and vision and mission of a company. STIKOM Bali has a different organizational culture from other private universities. The main issue at this time is the relationship between education and training and organizational culture on employee performance. Currently employees in universities have an agenda for training and education activities, this is done to improve company performance. Increased companies are influenced by adequate and reliable human resources in carrying out activities. Education and training as well as organizational culture in universities have a considerable influence on the performance of employees themselves. From the urgency, it was felt necessary to do a training on organizational culture education in order to have a positive impact on employee performance at STIKOM Bali. This study uses a single case study with a descriptive qualitative approach. Primary sources are obtained from interviews, observation and documentation. From the results of research that has been found that training and education in organizational culture has a positive impact on employee performance at STIKOM Bali. This will be a reference in human resource development and affect the improvement of the company's vision and mission.